Efficient computation of free energy surfaces of chemical reactions using ab initio molecular dynamics with hybrid functionals and plane waves. Issue 19 (14th May 2020) - Mandal, Sagarmoy; Nair, Nisanth N.
Abstract: Ab initio molecular dynamics (AIMD) simulations employing density functional theory (DFT) and plane waves are routinely carried out using density functionals at the level of generalized gradient approximation (GGA). AIMD simulations employing hybrid density functionals are of great interest as it offers a more accurate description of structural and dynamic properties than the GGA functionals. However, the computational cost for carrying out calculations using hybrid functionals and plane wave basis set is at least two orders of magnitude higher than that using GGA functionals. Recently, we proposed a strategy that combined the adaptively compressed exchange operator formulation and the multiple time step integration scheme to reduce the computational cost by an order of magnitude [ J. Chem. Phys . 151, 151102 (2019)]. In this work, we demonstrate the application of this method to study chemical reactions, in particular, formamide hydrolysis in an alkaline aqueous medium. By actuating our implementation with the well‐sliced metadynamics scheme, we can compute the two‐dimensional free energy surface of this reaction at the level of hybrid‐DFT. This work also investigates the accuracy of the PBE0 (hybrid) and the PBE (GGA) functionals in predicting the free energetics of this chemical reaction. Abstract : Hybrid DFT functionals are more accurate than the GGA functionals, but the former requires ∼100 times more computational time compared to the latter when used with plane wave basis set. Here we demonstrate that by using the recently proposed r‐RESPA+ACE method, which can speed‐up hybrid DFT based MD calculations ∼7 times, free energy calculations of chemical reactions using hybrid DFT functionals and plane waves are indeed doable.